Community-based productive zakat: Evidence from Bengkalis Regency - Mukhlis, Mukhlis; Romi, Muhammad; Johari, Fuadah (Review of Islamic Social Finance and Entrepreneurship, 2026)
Purpose – This study aims to comprehensively analyze the problems, solutions, and strategies in implementing community-based productive zakat at the National Amil Zakat Agency (Badan Amil Zakat Nasional, BAZNAS) Bengkalis to improve the welfare of mustahiq sustainably. Methodology – This study uses the ANP method with Super Decisions software, which is then analyzed through the supermatrix stage to obtain priority values and agreement values to measure the level of consistency of respondents assessments. The research sample consisted of 11 respondents, including three experts, four academics, and four stakeholders. Findings – The results show that the muzakki problem cluster is a top priority, with a respondent agreement level of 83.53%, especially related to the practice of individual zakat distribution and low literacy. On the mustahiq side, the main problem lies in the incomplete coverage of zakat recipients and suboptimal business mentoring. From the perspective of zakat management, the lack of professional human resources is the main problem. Priority solutions include optimizing the role of the community, strengthening institutional socialization, and improving monitoring systems. The main recommended strategy is trustworthy and professional management, based on transparency and accountability. Implications – This study enriches the literature on productive zakat by integrating the perspectives of empowerment and maqasid al-Sharia in the context of coastal and island areas. These findings provide a policy direction for strengthening adaptive, measurable, and sustainable community-based zakat governance. Originality – The novelty of this research lies in the community-based analysis in an archipelagic region that has been relatively understudied and the use of ANP to identify priority problems, solutions, and strategies systematically and measurably in the context of zakat.